Role of the 5' upstream sequence and tandem promoters in regulation of the rpsU-dnaG-rpoD macromolecular synthesis operon. - Nesin, M (1988)
Bal31 exonuclease deletion analysis and transposon Tn5 mutagenesis of the 5' regulatory region of the rpsU-dnaG-rpoD macromolecular synthesis operon fused to the chloramphenicol acetyltransferase gene (pGLR301) demonstrated that sequences 5' to the operon promoters were not involved in operon transcriptional regulation and that the three tandem promoters P1, P2, and P3 were functionally independent. P2 was the strongest promoter, and P3 was the weakest. P1, P2, and P3 acting in combination appeared to be stronger than the individual promoters.